2013
DOI: 10.1016/j.neuropharm.2013.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Divergent circuitry underlying food reward and intake effects of ghrelin: Dopaminergic VTA-accumbens projection mediates ghrelin's effect on food reward but not food intake

Abstract: Obesity has reached global epidemic proportions and creating an urgent need to understand mechanisms underlying excessive and uncontrolled food intake. Ghrelin, the only known circulating orexigenic hormone, potently increases food reward behavior. The neurochemical circuitry that links ghrelin to the mesolimbic reward system and to the increased food reward behavior remains unclear. Here we examine whether VTA-NAc dopaminergic signaling is required for the effects of ghrelin on food reward and intake. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 64 publications
8
72
0
6
Order By: Relevance
“…We focused our attention on DA signaling from the VTA to the NAcC, a pathway known to influence food intake and motivated behavior (Cone et al, 2014;Roitman et al, 2004;Vucetic and Reyes, 2010;Wanat et al, 2010). Several feeding-related peptides modulate VTA to NAc DA neurotransmission, including leptin (Krugel et al, 2003) and ghrelin (Cone et al, 2014;Skibicka et al, 2013). Here, we found that VTA AmyR activation reduces NAcC D1/D2 receptor activation to decrease feeding.…”
Section: Discussionmentioning
confidence: 89%
“…We focused our attention on DA signaling from the VTA to the NAcC, a pathway known to influence food intake and motivated behavior (Cone et al, 2014;Roitman et al, 2004;Vucetic and Reyes, 2010;Wanat et al, 2010). Several feeding-related peptides modulate VTA to NAc DA neurotransmission, including leptin (Krugel et al, 2003) and ghrelin (Cone et al, 2014;Skibicka et al, 2013). Here, we found that VTA AmyR activation reduces NAcC D1/D2 receptor activation to decrease feeding.…”
Section: Discussionmentioning
confidence: 89%
“…In addition to leptin (Fulton et al, 2006), the stomach-derived orexigenic hormone ghrelin has been shown to have an important role in motivation for food reward in rodents. Ghrelin increases lever-pressing for sucrose in a progressive ratio operant responding paradigm (Skibicka et al, 2012a), an effect that appears to involve the VTAaccumbens dopaminergic pathway (Skibicka et al, 2013) as well as mu-opioid-sensitive pathways (Skibicka et al, 2012b). Interestingly, ghrelin's effects on food reward behavior and simple intake of chow exerted at the level of the VTA appear to be controlled by divergent circuitry: although accumbens dopamine (Skibicka et al, 2013) and VTA mu-opioid pathways (Skibicka et al, 2012b) have an important role in food reward, they do not alter food intake.…”
Section: Neurobiology Of the Reward Pathways And The Overlap And Intementioning
confidence: 99%
“…Ghrelin increases lever-pressing for sucrose in a progressive ratio operant responding paradigm (Skibicka et al, 2012a), an effect that appears to involve the VTAaccumbens dopaminergic pathway (Skibicka et al, 2013) as well as mu-opioid-sensitive pathways (Skibicka et al, 2012b). Interestingly, ghrelin's effects on food reward behavior and simple intake of chow exerted at the level of the VTA appear to be controlled by divergent circuitry: although accumbens dopamine (Skibicka et al, 2013) and VTA mu-opioid pathways (Skibicka et al, 2012b) have an important role in food reward, they do not alter food intake. The midbrain reward circuitry is also targeted by circulating anorexigenic peptides, several of which have been shown to suppress food-motivated behavior, including GLP-1 (Dickson et al, 2012) and insulin (Figlewicz et al, 2008).…”
Section: Neurobiology Of the Reward Pathways And The Overlap And Intementioning
confidence: 99%
“…Furthermore, palatable food-mediated CPP was increased by ghrelin, but blocked by a GHS-R1a antagonist or genetic deletion of GHS-R1a or ghrelin (Egecioglu et al, 2010; Perello et al, 2010; Disse et al, 2011). Ghrelin-mediated increase in NAc dopamine signaling has been shown to play a crucial role in reward sensitivity since dopamine D1R and D2R antagonists in the NAc attenuate the ability of VTA ghrelin to increase operant responding for sucrose (Skibicka et al, 2013). These studies indicate that ghrelin increases reward sensitivity, which is most likely through its effects on VTA dopaminergic neurons.…”
Section: Ghrelinmentioning
confidence: 99%